Advanced treatment of biologically pretreated coking wastewater by electrochemical oxidation using Ti/RuO2–IrO2 electrodes. Issue 8 (7th January 2013) - He, Xuwen; Chai, Zhen; Li, Fuping; Zhang, Chunhui; Li, Dong; Li, Jing; Hu, Jianlong
Abstract: Background: Electrochemical oxidation has attracted wide attention in wastewater treatment because of its strong oxidation performance and ease of control. This work investigated the feasibility of electrochemical treatment using a Ti/RuO2 –IrO2 anode as an advanced treatment of coking wastewater. The influential operating factors including current density (9.6–108.2 mA cm −2 ) and electrode gap (0.5–2.5 cm) were evaluated . Results: The current density and electrodes gap had significant effects on COD and NH4 + ‐N removal and the energy consumption. The degradation of COD and NH4 + ‐N followed pseudo‐first‐order kinetics. In most experiments, high levels of NH4 + ‐N removal (NH4 + ‐N removal ratio > 95%) was achieved along with moderate mineralization (COD removal ratio: 60–80%). COD (178.0–285.0 mg L ‐1 ) and NH4 + ‐N (55.0–76.0 mg L ‐1 ) were degraded by 62% and 96%, respectively, at the optimum conditions (electrode gap: 0.5 cm, current density: 15.6 mA cm −2 ) after 60 min treatment. Under this optimal condition, the corresponding energy consumption was 8.60 kWh m ‐3 for effluent meeting the discharge standards. Furthermore, gas chromatography–mass spectrometry (GC‐MS) analysis indicated that this technique could be employed to eliminate bio‐refractory and toxic compounds such as phenanthrene, indole, quinoline and pyrimidine in coking wastewater . Conclusion: Ti/RuO2 –IrO2 anode systems were confirmed to be effective in advanced treatment of biologically pretreated coking wastewater. © 2012 Society of Chemical Industry